Analisis Tingkat Konsumsi Energi dan Protein pada Ibu Hamil Anemia di Wilayah Kerja Puskesmas Danau Panggang - Norhasanah Norhasanah; Siti Aisyah Solechah (Jurnal Kesehatan Indonesia, 2022)
Anemia in pregnant women is still one of the national problems because it reflects the value of the socio-economic welfare of the community. It also has large influence on the quality of human resources. Anemia of pregnancy is called 'potential danger to mother and child', and thereby anemia requires attention from all parties involved in health services at the forefront. This descriptive analytic study used a cross-sectional design, with a total sample of 40 anemic pregnant women. This study used a purposive sampling method. It was conducted in the working area of the Puskesmas Danau Panggang. The variables observed in this study were energy and protein consumption levels in anemic pregnant women. The data were analyzed using descriptive analysis, presented in the form of a frequency distribution table. The results showed that the energy consumption level of anemic pregnant women was mostly in the severe deficit category, namely 95% (38) of anemic pregnant women. Based on this number, most of them (i.e., 58% or 22 anemic pregnant women) had the energy consumption level between 30% and 49% RDA. Meanwhile, the level of protein consumption of most anemic pregnant women was in the severe deficit category, i.e., 87,5% (35) anemic pregnant women. Based on this number, the majority, namely 60% (21) pregnant women with anemia, Most of anemic pregnant women (60% or 21 women) had the protein consumption level between 30% and 49% of the RDA.